A study on the effects of language and visual art integrated teaching on language learning performance and satisfaction of ethnic minority students in China - Zhang, Yao; Jia, Simeng (Frontiers in Psychology, 2022)
Innovative technological products appear in students’ environments. Information explosion and popularity are affecting thoughts, and a large amount of information fill life through Internet, television, movies, advertisements. This phenomenon transforms reading from pure words into image. The current study was conducted using experimental design model. A total of 188 ethnic minority students in Hebei Province participated in the experimental study. The experimental group went through language and visual art integrated instruction, while the control group maintained traditional teaching. The experimental study lasted for 20 weeks (3 hours per week). The research results showed that 1. Spoken and written artistic conception was displayed through artistic expression. Ethnic minority students’ differences in language skills and artistic expression were found as the factors effective in the production process. These made the work richer and more diversified. 2. After joining several lessons, ethnic minority students were found to be getting better in terms of integrating art vocabulary into their conversation, and 3. Language and visual art integrated teaching input was story content which was received through “listening”, outputs were individual opinions through “speaking”. Their thoughts were presented through “painting”. The creation process operated in the brain and reflected differences in terms of their thinking skills, vocabulary organizational skills, language use, and creativity. Based on the results this study is expected to improve ethnic minority students’ language proficiency, enhance their artistic culture, understanding and attitude toward language and literature.